Phosphatidic acid, phospholipase D and tumorigenesis(☆) - Gomez-Cambronero, Julian (2013)
Phospholipase D (PLD) is a membrane protein with a double role: maintenance of the structural integrity of cellular or intracellular membranes and involvement in cell signaling through the product of the catalytic reaction, PA, and through protein–protein interaction with a variety of partners. Cross-talk during PLD signaling occurs with other cancer regulators (Ras, PDGF, TGF and kinases). Elevation of either PLD1 or PLD2 (the two mammalian isoforms of PLD) is able to transform fibroblasts and contribute to cancer progression. Elevated total PLD activity, as well as overexpression, is present in a wide variety of cancers such as gastric, colorectal, renal, stomach, esophagus, lung and breast. PLD provides survival signals and is involved in migration, adhesion and invasion of cancer cells, and all are increased during PLD upregulation or, conversely, they are decreased during PLD loss of function. Even-though the end results of PLD action as relates to downstream signaling mechanisms are still currently being elucidated, invasion, a pre-requisite for metastasis, is directly affected by PLD. This review will introduce the classical mammalian PLD’s, PLD1 and PLD2, followed by the mechanisms of intracellular regulation and a status of current investigation in the crucial involvement of PLD in cancer, mostly through its role in cell migration, invasion and metastasis, that has grown exponentially in the last few years.